Digital Platform for Creating Personalized Adaptive Online Courses - N. V. Komleva; D. A. Vilyavin (Открытое образование (Москва), 2020)
The purpose of the research is to develop a digital platform for creating personalized adaptive online courses that can integrate into the university’s e-learning environment. The Digital Tutor platform is designed to provide the online learning process with tools that allow for the adaptation of the content of the electronic course in accordance with the individual level of student competency through adaptive testing tools in order to achieve the level of student competency established by educational and professional standards.Materials and research methods. The research methodological base consists of methods and technologies of system analysis and knowledge management. Conclusions and provisions of the work are based on the analysis of domestic and foreign literature on the use of digital technologies in education. In preparing the article, materials obtained by the authors during the scientific and practical development of the prototype of the Digital Tutor platform were used to create personalized adaptive online courses at Plekhanov Russian University of Economics.Results. The digital platform for hosting the repository of educational objects and the online courses themselves is available on the University’s information resources with the possibility of integration into the University’s electronic educational environment. The implementation of this project will allow: students and the audience to use educational content prepared on the basis of relevant educational material, as well as to participate in its creation and discussion; to develop more dynamic and high-quality training courses that contribute to the formation of the required competencies among students and the audience; significantly reduce the burden on lecturers when working with remote students, free up more time for updating the training material, the formation of practical and design tasks; implement the concept of personalization of training - the creation of educational material aimed at a particular student; provide support for the creation and updating of their own MOOC; transform the system of continuing education to the requirements and needs of the business; respond ahead of time to the needs of society for qualified personnel for the digital economy.Conclusion. A new model for the implementation of online education has been proposed and tested, which consists in the automatic construction of online courses from the educational objects of the repository in accordance with the monitoring of its activities and a personal trajectory to achieve the required learning outcomes. The concept of transformation of the model of online education is based on the creation of a modern educational based on advanced digital, intelligent technologies. Compared with existing analogues, the project has competitive advantages in the implementation of a new business model of education, based on the availability of a mechanism for automatic updating of educational content and preparing courses on the basis of a repository of educational objects that form the necessary competencies in accordance with the Federal State Educational Standard and approved professional standards.